Potensi Paparan Media Sosial pada Gejala Hiperaktivitas Remaja di Kota Jayapura - Asriati, Asriati; Pamangin, Lisda Oktavia Madu; Juniasti, Helen Try; Adimuntja, Natalia Paskawati; Violita, Fajrin; Nurdin, Muhammad Akbar; Mayabubun, Maria Papuana Natalia; Taa, Marlessy Christina (Universitas Malahayati, 2026)
ABSTRACT Social media use (SMU) among children and adolescents has increased since the Covid-19 pandemic. SMU can become addictive and is related to the emergence of health problems, such as symptoms of attention deficit hyperactivity disorder (ADHD). This study aims to determine the relationship of SMU among adolescents in Jayapura to the risk of attention deficit hyperactivity disorder (ADHD). This was a cross-sectional survey in August 2024. The samples in this study were from 301 adolescents aged 15-19 years at SMAN 2 Jayapura. Data analysis using the Pearson correlation test. Most respondents were female (50,8%), and most respondents parent jobs were Civil Servants (38,9%). A total of 46 people (15.28%) of respondents had ADHD symptoms, women were more likely to show ADHD symptoms (18,2%), and as many as 33 people (10.96%) of adolescents who experienced social media addiction were in the severe category. The correlation between social media addiction and ADHD symptoms is positive with a moderate correlation strength (r = 0.5419; p-value 0.000), so there is a significant relationship between social media addiction and the incidence of ADHD. Adolescents who experience increased social media addiction also experience increased ADHD symptoms. Appropriate management and policies are needed in the prevention and control of social media usde and ADHD in children and adolescents. Parents and schools should pay more attention to adolescents with internet and social media addiction, and ADHD symptoms should be carefully evaluated. Keywords: Social Media, ADHD, Adolescents. ABSTRAK Penggunaan media sosial (SMU) di antara anak-anak dan remaja telah meningkat sejak pandemi Covid-19. SMU dapat menjadi adiktif dan terkait dengan munculnya masalah kesehatan, seperti gejala gangguan hiperaktif defisit perhatian (ADHD). Penelitian ini bertujuan untuk menentukan hubungan penggunaan media sosial di kalangan remaja di Jayapura dengan risiko ADHD. Penelitian ini adalah survei cross-sectional pada Agustus 2024. Sampel dalam penelitian ini berasal dari 301 remaja berusia 15-19 tahun di SMAN 2 Jayapura. Analisis Data menggunakan uji Korelasi Pearson. Sebagian besar responden adalah perempuan (50,8%), dan sebagian besar responden pekerjaan orang tua adalah pegawai negeri sipil (38,9%). Sebanyak 46 orang (15,28%) responden mengalami gejala ADHD, remaja perempuan lebih cenderung menunjukkan gejala ADHD (18,2%), dan sebanyak 33 orang (10,96%) remaja yang mengalami kecanduan media sosial ada di kategori berat. Korelasi antara kecanduan media sosial dan gejala ADHD positif dengan kekuatan korelasi sedang (r = 0,5419; p-value 0,000), sehingga ada hubungan yang signifikan antara kecanduan media sosial dan kejadian ADHD. Remaja yang mengalami peningkatan kecanduan media sosial juga mengalami peningkatan gejala ADHD. Manajemen dan kebijakan yang tepat diperlukan dalam pencegahan dan kontrol penggunaan media sosial dan risiko ADHD pada anak -anak dan remaja. Orang tua dan sekolah harus lebih memperhatikan remaja dengan kecanduan internet dan media sosial, dan gejala ADHD harus dievaluasi dengan cermat. Kata Kunci: Media Sosial, ADHD, Remaja.